Solvent slurries in bitumen production - Wolff, Vining (Knovel, 2011)
"The method for extracting bitumen from oil sands currently used in commercial mining operations is a flotation process in which oil sands are combined with hot water and the slurry is aerated. This method generally is referred to as the Clark hot water process"--Description from Knovel site.